Pendidikan Perempuan dalam Hadis Tematik dan Filsafat Pendidikan Islam Seyyed Hossein Nasr - Nursyahbani, Iqbal; Sholihin, Sholihin; Fatahillah, Denta Fatwa; Amrulloh, Amrulloh (Dirasat: Jurnal Manajemen dan Pendidikan Islam, 2024)
Islam is a religion known for elevating the status of women. However, there are hadiths that textually appear to still have gender discrimination or bias in education. At first glance, this seems to be at odds with the vision of Islamic education which seeks to equalize education regardless of gender. In addition, philosophically, education is a right for every individual regardless of gender. The purpose of this study is to collect hadiths related to women’s education, then understand and analyze these hadiths using a thematic and philosophical approach. This study uses content analysis and descriptive analysis methods in studying hadiths related to women’s education. The analytical tool applied is the Islamic educational philosophy analysis approach proposed by Seyyed Hossein Nasr. The results of the study show that women's education is a new civilization built by the Prophet Muhammad which can be known through hadiths related to women’s education. There is no specific gender discrimination in education as a new civilization that is being built.